PENGEMBANGAN SISTEM INFORMASI PARIWISATA KOTA PALEMBANG BERBASIS MOBILE ANDROID - Mira Afrina; Ali Ibrahim; Tumpol S Simarmata (Universitas Sriwijaya, 2016)
AbstractInformation and communication technologies, the growing human needs will push the information quickly and accurately. As in the field of tourism, fast and accurate information is needed in order to facilitate the tourists to reach tourist destinations that will be targeted. Promotion and marketing of tourist attraction which was conducted by the Department of culture and tourism of the city of Palembang was a print media such as mass media, booklets with tour maps are dynamic but not this method is still not enough to convey the information accurately to tour domestic and foreign tourists. Therefore, through the design and development of information system of tourism based android mobile is able to facilitate tourists in finding existing tourist information in the city of Palembang. This system utilizes the internet and technology Location Based Service (LBS) using the GPS (Global Positioning System) which was built on the Android platform. As for the system development methods used is RUP (Rational Unified Proces) using the concept of the Unified Modelling Language (UML), while the diagram is the Use Case diagrams, Activity diagrams, Sequence Diagrams, and Class diagrams. Information in the form of tourist maps are displayed in the Library of Google Maps Apis. The result of the final project of tourism information system Architecture-based Android Mobile with the approach of Beriorentasi objects on the Department of culture and tourism of the city of Palembang is capable of displaying travel information, tourism as well as the supporting means of tourist sites in the form of a dynamic tourism maps.Keywords : information systems, tourism, Palembang, mobile android, GPS (Global Positioning System), RUP (Rational Unified Proces).AbstrakTeknologi, informasi dan komunikasi yang semakin berkembang mendorong kebutuhan manusia akan informasi yang cepat dan akurat. Seperti dalam bidang pariwisata, informasi yang cepat dan akurat dibutuhkan agar mempermudah wisatawan untuk mencapai tujuan wisata yang akan dituju. Promosi dan pemasaran daya tarik wisata yang dilakukan oleh Dinas Kebudayaan dan Pariwisata kota Palembang masih berupa media cetak seperti media massa, booklet dengan peta wisata yang tidak dinamis namun metode ini masih belum cukup untuk menyampaikan informasi wisata secara akurat kepada wisatawan domestik dan wisatawan mancanegara. Oleh karena itu melalui hasil penelitian ini dapat mempermudah wisatawan dalam mencari informasi wisata yang ada di kota Palembang. Sistem ini memanfaatkan internet dan teknologi Location Based Service (LBS) dengan menggunakan GPS (Global Positioning System) yang dibangun diatas platform Android. Adapun metode pengembangan sistem yang digunakan adalah RUP (Rational Unified Proces) dengan menggunakan konsep Unified Modelling Language (UML), sedangkan diagram yang digunakan adalah Use Case Diagram, Activity Diagram, Sequence Diagram dan Class Diagram. Informasi berupa peta wisata ditampilkan dengan Library Google Maps Apis. Hasil dari penelitian Sistem Informasi Pariwisata Berbasis Mobile Android Pariwisata Kota Palembang ini mampu menampilkan informasi wisata, sarana pendukung wisata serta lokasi wisata dalam bentuk peta wisata yang dinamis.Kata kunci : Sistem informasi, pariwisata, Palembang, mobile android, GPS (Global Positioning System), RUP (Rational Unified Proces)